Number and depth of epithelial folds in skin of crossbred cattle - SAXENA, S K; PAREKH, H K B; MALIK, M R (The Indian Journal of Animal Sciences, 2013)
The study of skin epithelial folds in crossbred cattle revealed significantly fewer number of folds during summerthan during winter and monsoon indicating expansion of skin for adaptation. The differences due to genetic group, body region and season X genetic group interaction were not significant. There was a significant reduction in epiLhelial fold with advancing age. A significantly reduced deplh of folds during monsoon only indicated the role of humidity. Significantly deeper folds in JFL group was noticed. In summer the greater depth of folds in 1/2 Jersey X 1/4 Holstein-Friesian X 1/4 Gir group indicated higher adaptive value the in 1/2 Holswin-Friesian X Jersey X 1/4 Gir group having shallower folds.